2005
DOI: 10.1093/aje/kwi228
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcium Score and Coronary Heart Disease Events in a Large Cohort of Asymptomatic Men and Women

Abstract: Coronary artery calcium (CAC), a measure of subclinical coronary heart disease (CHD), may be useful in identifying asymptomatic persons at risk of CHD events. The current study included 10,746 adults who were 22-96 years of age, were free of known CHD, and had their CAC quantified by electron-beam tomography at baseline as part of a preventive medical examination at the Cooper Clinic (Dallas, Texas) during 1995-2000. During a mean follow-up of 3.5 years, 81 hard events (CHD death, nonfatal myocardial infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
177
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(200 citation statements)
references
References 41 publications
9
177
2
6
Order By: Relevance
“…Of note, a large body of evidence renders the absence of calcification a 5-year safety window, with a 0.10% annual risk of events (2,32,(37)(38)(39)(40)(41).…”
Section: Mini-reviewmentioning
confidence: 99%
“…Of note, a large body of evidence renders the absence of calcification a 5-year safety window, with a 0.10% annual risk of events (2,32,(37)(38)(39)(40)(41).…”
Section: Mini-reviewmentioning
confidence: 99%
“…1 Autopsy studies have demonstrated that both aortic and coronary atherosclerosis have long subclinical phases [2][3][4][5][6] and in such studies, HTN is associated with greater prevalence and extent of aortic and coronary atherosclerosis. 3,5,6 A growing body of evidence has linked subclinical coronary 7 and aortic 8 -10 atherosclerosis to increased risk for clinically overt CVD, suggesting that early diagnosis and treatment of atherosclerosis in the preclinical stage may reduce CVD sequelae such as myocardial infarction and stroke. However, beyond autopsy studies, our understanding of the relationship between age, sex, and HTN with aortic atherosclerotic burden is incomplete.…”
mentioning
confidence: 99%
“…Nevertheless, some controversy surrounds this score: it does not completely rule out atherosclerosis as non-calcified fibrolipid plaque, such as that shown in Fig 3, can be missed. 18 Calcium score was initially developed for use in asymptomatic patients and although the false-negative rate associated with scores of zero is not known, recent studies have identified significant CAD in acute symptomatic patients with a score of zero. 19,20 Medical therapy should be optimised and imaging considered on a case by case basis -some centres will still proceed to CTCA particularly in young symptomatic patients who are more likely to have non-calcific atherosclerosis.…”
Section: Outcome 1: Calcium Score Of Zeromentioning
confidence: 99%